Upaya meningkatkan aktivitas dan hasil belajar Qur’an Hadits materi Q.S. Al-kafirun dan Q.S. Al-ma’un melalui metode word square siswa kelas v MIN 11 Aceh Barat Daya - Hazimah, Hazimah (Universitas Serambi Mekkah, 2020)
This research is motivated by the conditions of learning the Qur'an Hadith in schools, where student learning outcomes are still relatively low. In this case the researchers tried to overcome these problems through the application of the Word Square Method. The application of the Word Square method in the teaching and learning process is expected to help students' understanding in learning the Qur'an's Hadith, so that student learning outcomes can be improved. The formulation of the problem in writing this thesis is (1) How is the application of the Word Square Method in learning the Qur'an of Hadith the subject of Al-Kafirun and Al-Ma’un in class V MIN 11 students of Southwest Aceh Aceh 2019/2020 Academic Year? (2) How to improve the learning outcomes of the Qur'an's Hadith subject matter of Al-Kafirun and Al-Ma’un through the application of the Word Square Method for V MIN grade 11 Southwestern stu-dents in 2019/2020 Academic Year? As for the objectives of this study are (1) Describe the application of the Word Square Method in learning the Qur'an Hadith subject matter of Al-Kafirun and Al-Ma’un class V students MIN 11 Southwest Aceh Aceh Southwestern School Year 2019/2020. (2) Describe the improvement in learning outcomes of the Qur'an Hadith subject matter of Al-Kafirun and Al-Ma’un through the application of the Word Square Method for students of class V MIN 11 Southwest Aceh Aceh 2019/2020 Academic Year. This research uses Classroom Action Research in two cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The target of this research is grade V MIN 11 Aceh Barat Daya students. Techniques used in collecting data include tests, observations, field notes, and documentation. Analysis of the data used includes data reduction, data presentation, and drawing conclusions. Indicators of success in this study if the mastery of students' material reaches 70% of the goals that should be achieved, with a KKM value of 70. The results of the study indicate that the application of the Word Square Method using a six-stage structure can improve student learning outcomes in the Qur'an's Hadith. This is evidenced by an increase in student learning outcomes from Cycle I to Cycle II, namely the average value of learning outcomes at the end of Cycle I is 57.50 (58.33%) which is in good criteria, whereas in the final Cycle II test is 67.50 (75.00% ) and are in very good criteria. From these data it can be seen that the application of the Word Square method can improve the learning outcomes of the Qur'an Hadith Al-Kafirun and Al-Ma’un class V MIN 11 Aceh Barat Daya Academic Year 2019/2020 Academic Year.